Evaluating Organic Farms’ Business Models for Profit Maximization in Laguna, Philippines - Aquino, Eliza Catelo; Shimoguchi, Nina Nocon; Hatanaka, Katsumori (Sharia Agribusiness Journal, 2025)
ABSTRACTWith the importance of organic agriculture (OA) in providing safer food for the consumers, reliable and harmless production for the farmers and the environment, there is a need for more adopters. In the Philippines, the government provided and implemented various programs to convince farmers to adopt OA. But most of the farmers who have adopted OA are more focused on its health and environmental benefits, forsaking its profit benefits. Advantages must be explored and presented focusing on the most profitable business model. With this, the study aims to create a business model canvas of organic farms in Laguna, Philippines and to help farmers easily and efficiently assess how they will be able to make profit albeit fulfilling a need and catering value to their customers, further persuading more farmers to adopt OA. This qualitative study used Historically Structured Inviting on 36 organic farmers in Laguna, Philippines, mostly small-scale farms. Interviewed and observed at least twice between 2017 to 2023. Upon in-depth interviews, risks in production, marketing, financial, and human resources were identified. Market opportunities were assessed. Business models were analyzed which leads to a creation of a business model canvas of OA in Laguna, Philippines.Keywords: organic agriculture; business model canvas; qualitative